Analysis of brain necrosis and secondary cancers after proton beam therapy for pediatric intracranial tumors: a single-center retrospective study - Mizumoto, Masashi; Fukushima, Hiroko; Oshiro, Yoshiko; Saito, Takashi; Muroi, Ai; Yamaki, Yuni; Hosaka, Sho; Inaba, Masako; Ishiguro, Toshitaka; Harada, Masahiko; Niitsu, Hikaru; Ishida, Toshiki; et al. (Frontiers in Oncology, 2025)
BackgroundProton beam therapy (PBT) is increasingly used for pediatric intracranial tumors due to lower long-term radiation-associated toxicities. However, data on late adverse effects, particularly brain necrosis and intracranial secondary cancer, remain limited. The aim of this study is to evaluate the incidence of these events following PBT in pediatric patients treated at a single center.ProcedureWe retrospectively reviewed the medical records of 189 patients under 20 years of age who received PBT for intracranial tumors between 1991 and 2023. Clinical information, irradiation parameters, concurrent chemotherapy, and follow-up outcomes were collected. Brain necrosis and intracranial secondary cancers were assessed based on events presenting with grade ≥2 clinical symptoms.ResultsAmong 151 patients with sufficient follow-up data (median follow-up: 41.7 months), two cases of brain necrosis (1.3%) and two cases of intracranial secondary cancer (1.3%) were identified. The 5-year cumulative incidence was 2.3% (95% CI: 0-5.4%) for brain necrosis and 2.7% (95% CI: 0-6.4%) for intracranial secondary cancer. These respective incidence rates were similar for patients followed for more than two years (n=94), and slightly higher at 2.7% and 3.1% for those receiving a total dose >50 Gy (n=134). Among patients treated with PBT alone (n=125), the incidence was 1.7% for brain necrosis and 3.6% for secondary malignancy.ConclusionsThis single-center retrospective study shows a low incidence of brain necrosis and secondary malignancy following PBT for pediatric patients with intracranial tumors. These findings indicate a favorable long-term safety profile of PBT in this population.